Growth-associated protein (GAP-43) in terminal Schwann cells of rat Pacinian corpuscles - Dubovy, P; Aldskogius, H (Neuroreport, 1996)
Growth-associated protein (GAP-43) immunoreactivity was examined in Pacinian corpuscles of intact neonatal and adult rats as well as after denervation and reinnervation in adult rats. All immature Pacinian corpuscles were GAP-43 immunoreactive (GAP-43+) in their inner cores while only 46 +/- 5.6% of the mature corpuscles exhibited GAP-43+ inner cores. The frequency of GAP-43+ inner cores increased to 90 +/- 7.2% after their permanent denervation. The expression of GAP-43 in the inner cores was reduced by contact with regrowing axons, but 38 +/- 5.3% of Pacinian corpuscles retained GAP-43+ in their inner cores following reinnervation. These results indicate that GAP-43 regulation is not confined only to axons but also involves some extra-axonal cues, and support a role for this protein in the process formation by terminal Schwann cells.
Keywords: růstové látky; Animals, Newborn; Nerve Crush; Aging; regenerace nervu; potkani Sprague-Dawley; membránové glykoproteiny; proteiny nervové tkáně; nervus ischiadicus; Schwannovy buňky; Sciatic Nerve; novorozená zvířata; krysa rodu Rattus; axony; Animals; GAP-43 Protein; Nerve Regeneration; zvířata; Membrane Glycoproteins; Rats; stárnutí; Growth Substances; Schwann Cells; protein GAP-43; rozdrcení nervu; Axons; Nerve Tissue Proteins; Rats, Sprague-Dawley